Формирование базы данных термодинамических свойств сложных эфиров жирных кислот биодизельных топлив в газовой фазе (часть 2) - Левтеров, Антон Михайлович; Левтеров, Александр Антонович; Левтерова, Людмила Ивановна (НТУ "ХПИ", 2016)
В результате аппроксимации дискретных табличных данных о термодинамических и термохимических свойствах двадцати двух метиловых и этиловых эфиров высших жирных кислот получены коэффициенты полиномов, описывающих основные термодинамические характеристики этих веществ в функции температуры на интервале 300 – 3000 К. Таким образом восполняется отсутствие сведений о термодинамических свойствах целого ряда биодизельных топлив, получаемых из различных растительных масел, которое затрудняет численное моделирование рабочих процессов поршневых двигателей с самовоспламенением.

Numerical researches of the working processes of piston engines with self-igniting fuel mixture working on biodiesel have been hampered by the lack of information on the thermodynamic characteristics of the high-temperature components of this fuel. In the second part of the paper we complete the task of forming the database of thermodynamic characteristics of twenty two complex methyl and ethyl esters of eleven higher fatty acids chemically bound in the biodiesel in various combinations. The combinations of the fuel esters depend on the type of vegetable oil from which the biodiesel is obtained, and the mass fraction of each constituent ester. The aim is to derive an approximate analytic dependence on the temperature of the main thermodynamic values (such as isobaric heat capacity, enthalpy and entropy in the temperature range 300 – 3000) for a number of biodisel fuels.
Forming database of thermodynamic properties of fatty acid esters of biodiesel fuel in the gas phase (part 2)
Keywords: биотоплива; растительные масла; математическое моделирование; рабочий процесс; термохимические свойства; полином; biofuels; fatty acid esters; vegetable oils; mathematical modeling